An Ethnography of the Provincial: The Social Geography of Gentility in Elizabeth Gaskell's Cranford - Knežević, Borislav (1998)
Focuses on the social geography of gentility in Elizabeth Gaskell's `Cranford.' Emphasis on the structure of a small-town society run by women of the rentier class ; Novel's association with the practice and discourse of ethnography ; Exploration of the competing claims on the definition of what constitutes national modernity.
ENG